Crime prevention through digitalization - Dimovski Darko (Zbornik Radova Pravnog Fakulteta u Nišu, 2021)
Common crime prevention measures have not yielded the expected results. It is important to examine the possibilities of using the latest achievements in crime prevention. One of the available options is digitalization. Starting from the definition of digitalization as the use of digital technologies to change the business model and provide new opportunities for generating income and value, the author emphasizes that digitalization can be used as a measure to prevent crime. In this regard, some solutions for preventing crime through digitalization are embodied in the use of digital currencies, digital identities and signatures, smart devices, and mobile applications. The author elaborates on each of these solutions, focusing on specific crime prevention measures and examples from different countries worldwide. It may help crime prevention experts perceive digitalization as a measure for reducing the volume of crime. If the benefits of digitalization are put into good use, we can expect that the volume of property-related crimes, violence-related crimes and traffic delinquency will drop in the forthcoming period. On the other hand, the implementation of these measures may give rise to the commission of Internet-related crimes, thus leading to the increase in computer crime.